Overcoming the lack of oral availability of cyclic hexapeptides: design of a selective and orally available ligand for the integrin alpha v beta 3 - Weinmueller, Michael; Rechenmacher, Florian; Marelli, Udaya Kiran; Reichart, Florian; Kapp, Tobias G.; Raeder, Andreas F. B.; Di Leva, Francesco Saverio; Marinelli, Luciana; Novellino, Ettore; Munoz-Felix, Jose M.; Hodivala-Dilke, Kairbaan; Schumacher, Adi; et al. (Angewandte Chemie-International Edition, 2017)
Ahighly systematic approach for the development of both orally bioavailable and bioactive cyclic N-methylated hexapeptides as high affinity ligands for the integrin alpha v beta 3 is based on two concepts: a) screening of systematically designed libraries with spatial diversity and b) masking of the peptide charge with a lipophilic protecting group. The key steps of the method are 1) initial design of a combinatorial library of Nmethylated analogues of the stem peptide cyclo(d-Ala-Ala(5)); 2) selection of cyclic peptides with the highest intestinal permeability; 3) design of sublibraries with the bioactive RGD sequence in all possible positions; 4) selection of the best ligands for RGD-recognizing integrin subtypes; 5) finetuning of the affinity and selectivity by additional Ala to Xaa substitutions; 6) protection of the charged functional groups according to the prodrug concept to regain intestinal and oral permeability; 7) proof of biological effects in mice after oral administration.

From a helix to a small cycle: metadynamics-inspired alpha v beta 6 integrin selective ligands - Di Leva, Francesco Saverio; Tomassi, Stefano; Di Maro, Salvatore; Reichart, Florian; Notni, Johannes; Dangi, Abha; Marelli, Udaya Kiran; Brancaccio, Diego; Merlino, Francesco; Wester, Hans-Juergen; Novellino, Ettore; Kessler, Horst; et al. (Angewandte Chemie-International Edition, 2018)
The RGD-recognizing alpha v beta 6 integrin has only recently emerged as a major target for cancer diagnosis and therapy. Thus, the development of selective, low-molecular-weight ligands of this receptor is still in great demand. Here, a metadynamics-driven design strategy allowed us to successfully convert a helical nonapeptide into a cyclic pentapeptide (6) showing remarkable potency and alpha v beta 6 specificity. NMR and docking studies elucidated the reasons for the high affinity and selectivity of this compound, setting the ground for the rational design of new alpha v beta 6-specific small peptides or even peptidomimetics. In vivo PET imaging studies demonstrated the potential use of 6 for medical applications.

N-Methylation of isoDGR peptides: discovery of a selective alpha 5 beta 1-integrin ligand as a potent tumor imaging agent - Kapp, Tobias G.; Di Leva, Francesco Saverio; Notni, Johannes; Raeder, Andreas F. B.; Fottner, Maximilian; Reichart, Florian; Reich, Dominik; Wurzer, Alexander; Steiger, Katja; Novellino, Ettore; Marelli, Udaya Kiran; Wester, Hans-Juergen; et al. (Journal of Medicinal Chemistry, 2018)
Specific targeting of the integrin subtype alpha 5 beta 1 possesses high potential in cancer diagnosis and therapy. Through sequential N-methylation, we successfully converted the biselective alpha 5 beta 1/alpha v beta 6 peptide c(phg-isoDGR-k) into a potent peptidic RGD binding aSfil subtype selective ligand c(phg-isoDGR-(NMe)k). Nuclear magnetic resonance spectroscopy and molecular modeling clarified the molecular basis of its improved selectivity profile. To demonstrate its potential in vivo, c(phg-isoDGR-(NMe)k) was trimerized with the chelator TRAP and used as a positron-emission tomography tracer for monitoring alpha 5 beta 1 integrin expression in a M21 mouse xenograft.

Selective targeting of integrin alpha v beta 8 by a highly active cyclic peptide - Reichart, Florian; Maltsev, Oleg V.; Kapp, Tobias G.; Raeder, Andreas F. B.; Weinmueller, Michael; Marelli, Udaya Kiran; Notni, Johannes; Wurzer, Alexander; Beck, Roswitha; Wester, Hans Juergen; Steiger, Katja; Di Maro, Salvatore; et al. (Journal of Medicinal Chemistry, 2019)
Integrins play important roles in physiological and pathophysiological processes. Among the RGD-recognizing integrin subtypes, the alpha v beta 8 receptor is emerging as an attractive target because of its involvement in various illnesses, such as autoimmune diseases, viral infections, and cancer. However, its functions have, so far, not been investigated in living subjects mainly because of the lack of a selective alpha v beta 8 ligand. Here, we report the design and potential medical applications of a cyclic octapeptide as the first highly selective small-molecule ligand for alpha v beta 8. Remarkably, this compound displays low nanomolar alpha v beta 8 binding affinity and a strong discriminating power of at least 2 orders of magnitude versus other RGD-recognizing integrins. Peptide functionalization with fluorescent or radioactive labels enables the selective imaging of alpha v beta 8-positive cells and tissues. This new probe will pave the way for detailed characterization of the distinct (patho)physiological role of this relatively unexplored integrin, providing a basis to fully exploit the potential of alpha v beta 8 as a target for molecular diagnostics and personalized therapy regimens.

Novel cilengitide-based cyclic RGD peptides as alpha nu beta(3) integrin inhibitors - Meena, Chhuttan L.; Singh, Dharmendra; Weinmueller, Michael; Reichart, Florian; Dangi, Abha; Marelli, Udaya Kiran; Zahler, Stefan; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2020)
In this letter, we report a series of five new RGD-containing cyclic peptides as potent inhibitors to alpha nu beta(3) integrin protein. We have incorporated various unnatural lipophilic amino acids into the cyclic RGD framework of cilengitide, which is selective for alpha nu beta(3) integrin. All the newly synthesized cyclic peptides were evaluated in vitro solid phase binding assay and investigated for their binding behaviour towards integrin subtypes. All the cyclic peptides were synthesized in excellent yield following solution-phase coupling strategy. The cyclic RGD peptides 1a-e exhibited IC50 of 9.9, 5.5, 72, 11 and 3.3 nM, respectively, towards a alpha nu beta(3) integrin protein. This finding offers further opportunities for the introduction unusual amino acids into the cyclic peptide framework of cilengitide.
Keywords: Anticancer drugs; Cilengitide; Integrins; RGD cyclicpeptides